Hubungan Pemberian Asi Eksklusif Dengan Kejadian Stunting Pada Balita Di Desa Payaman Kecamatan Mejobo Kabupaten Kudus - Ainur, Syafrida; Novita, Rina; Wardani, Sukma (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2024)
Stunting is a child's growth disorder due to chronic malnutrition and recurrent infections, which characterized by a z-score value of less than -2.00 SD. Data on stunting toddlers in Payaman Village as of April 2023 are 18 cases. Stunting can be prevented through exclusive breastfeeding, where breast milk has higher levels of calcium and can be absorbed by the body well so that toddlers can avoid the risk of stunting. The aim of this research was to determine the relationship between exclusive breastfeeding and the incidence of stunting among toddlers in Payaman Village, Mejobo District, Kudus Regency. This type of research is quantitative research with a correlation design with cross sectional approach. Sampling technique used is purposive sampling with a total sample of 102 toddlers aged 13 â€“ 59 months. The data collection method was carried out by interviews and observation. Data analysis used the Fisher Exact Test and Odds Ratio tests. Results of this study shows a significant relationship between exclusive breastfeeding and the incidence of stunting in toddlers Â with Ï value of 0,049 and OR = 3,267. One of the indirect factors that can influence stunting is the provision of exclusive breastfeeding. It is important to provide exclusive breastfeeding to babies up to the age of six months to maintain health and prevent stunting.